ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2016 - Yuslinda Nasution (Jurnal Manajemen, 2017)
The purpose of this research want to examine the effect of Current Ratio, Debt to Equity Ratio, Total Assets Turnover, and Earning power to Profit Growth in Manufacturing Company of Consumer Goods Sector Industry registered in Indonesia Stock Exchange period 2011-2016 either partially or simultaneously. The sampling technique used in this research is purposive sampling. There are 20 companies that used during the research. Analytical method used is multiple linear regression by using SPSS 22 The results of this research shows that Current Ratio, Debt to Equity Ratio, Total Assets Turnover, and Earning power simultaneously significant influence to the profit growth of Manufacturing Company of Consumer Goods Sector Industry with a significant level of < 0,05. from the research also know of that partially Current Ratio, Debt to Equity Ratio, Total Assets Turnover have an influence a significant to profit growth, while Earning Power does not have significant influence to profit growth of Manufacturing Company of Consumer Goods Sector Industry